PEDOMAN FORMAT DOKUMENTASI PENGKAJIAN KEPERAWATAN ORANG DENGAN GANGGUAN JIWA (ODGJ) - Ike Puspa Adityas; Dony Setiawan Hendyca Putra (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2022)
Mental assessment is process of collecting data systematically documenting determine health status of people with mental disorders. Mental assessment documentation format must provided based on needs of health service facility and should pay attention to guidelines for design aspects of the documentation format covering physical, anatomical, and content aspects. Study aims produce documentary format guideline for assessment people with mental disorders based on standard design documentation format. Study used the literature review method using 14 articles with combination of the theme form design article and mental nursing assessment. The technique of collecting data by collecting articles through academic repositories and then applying reselection articles using inclusion and exclusion criteria. Results of study, physical aspect use HVS 70 gram, portrait orientation rectangle shape, A4, white paper with black ink. Anatomical aspect, there a heading that explains the identity of agency and identity of format including title of the documentation format, the introduction is included in the title format, the instruction is placed at the bottom left of format, body includes grouping, type and size of letters, color, margins, line spacing, and how to fill in. Close is approval room containing signature and name. Content aspects consist items of identity, reasons for entry, predisposition, physical examination, psychosocial, mental status, social relationships, preparation for going home, coping, spiritual, psychosocial and environmental, knowledge, medical aspects, nursing problems, and additional information. Research suggestions, the format of the mental disorders nursing assessment documentation can be used as a reference guide in health service agencies